Actively personalized vaccination trial for newly diagnosed glioblastoma - Hilf, Norbert; Platten, Michael; Deimling, Andreas von; Bunse, Lukas; Wick, Wolfgang; Capper, David (Nature, 2019)
In a phase I trial, highly individualized peptide vaccines against unmutated tumour antigens and neoepitopes elicited sustained responses in CD8+ and CD4+ T cells, respectively, in patients with newly diagnosed glioblastoma.
Published online 19 December 2018
Gesehen am 14.05.2019